The role of ultrasound and preparation in first-year medical students' learning lumbar spine anatomy and diagnostic skills. (March 2017) - Chan, Vivian; Curtis, Sarah; Flaum, Theodore; Terzella, Michael; Yao, Sheldon C.; Cheriyan, George
Abstract: Background: Ultrasound as an educational tool in preclinical medical education needs to be examined because of its broad and increasing use in medicine and its potential in enhancing students' anatomical knowledge and diagnostic skills. This study examines the role of ultrasound and preparation in first-year medical students' learning to identify and palpate lumbar spine landmarks. Methods: Surveys were collected from first-year medical students who attended the lumbar spine workshop. Students were randomly stratified into two groups: using ultrasound and not using ultrasound. Student-diagnosed lumbar spine somatic dysfunctions were assessed by two blinded physicians. Results: Three hundred and eighteen first-year students completed the survey. Sixty six percent (n = 104) of the students in the ultrasound group stated that ultrasound improved their physical examination skills. No significant difference existed between the ultrasound and non-ultrasound groups in confidence level in palpation, engagement level in workshop, nor accurately diagnosing lumbar somatic dysfunction. A significantly greater proportion of prepared students, compared to unprepared students, responded that the workshop helped with diagnosing and was engaging, and that ultrasound did or would improve physical examination skills (all p < 0.05). No significant difference was found between ultrasound and non-ultrasound groups, as well as between prepared and non-prepared groups, in physician assessment of student diagnosis. Conclusion: The study results can assist in the design of future studies and workshops on ultrasound in preclinical education. Our study suggests the need for further research exploring ultrasound's role in helping preclinical medical students acquire basic and advanced palpatory and diagnostic skills.